PENGARUH TOTAL ASET DAN PENDAPATAN TERHADAP LABA BERSIH PADA PERUSAHAAN SUB INDUSTRI APPAREL & TEXTILE RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021 – 2023 - Juwita, Rukmi; widiyawati, merisa gusti (LAND JOURNAL, 2025)
Growth in the textile and apparel industry in Q1 2023 willl experience a decline. Throughout 2023 there will be more than 5,000 employees affected who will have to be laid off and laid off from 6 companies because many imported textile products are cheaper and take over the domestic market and there is a decline in exports due to the weakening global economy. He aim of this research is to assess the influence of Total Assets and Income on Net Profit in Retail Apparel and Textile Sub—Industry Companies Listed on The Indonesian Stock Exchange. The method used in this research is a quantitative method with a sample technique using purposive sampling technique. The are 4 companies in the research sampel. The financial report is in the form of a quarterly financial report for an apparel and textile retals sub-industry company listed on the Indonesian Stock Exchange with a total sample of 48 research data. Data analysis was carried out using: normality test, Product Moment Correlation Test, Multiple Linier regression analysis, Coefficient of Determination test, t test, dan f test. The results of the t test carried out using IBM SPSS Statistics version 26 show that total assets have no influence on net profit partally, while total assets have a negatif and significant influence on the net profit partially. The results of the f test show that simultaneously total assets and income have an influence on net profit.